The Risk Factors in Pre-Eclampsi in Medan, Indonesia - Ritonga, Imelda Liana (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
High maternal mortality rate (MMR) in Indonesia is an indicator to be controlled.  The goal is to achieve less than 70 per 100,000 live births by 2030.  Preeclampsia is one problem induced the maternal deaths. It has been acknowledged there is some differences preeclampsia risk factors between regions. In this study, the reseracher want to identify the risk factors in preeclampsia cases in Medan, Indonesia. The study was restropective study using case study design.  The unit analysis was medical record patients with preeclampsia who admitted to one private hospital in Medan, fom January until June 2021. The risk factors found in this study did not support previous studies. The maternal age and maternal parity found not different between groups of patients with preeclampsia. However, the older age and more parity had more perinatal problems. Other conditions found in the patiens were anaemia, diabetes mellitus, hepatitis B, hypertension heart diseases with hypoalbumin, and HIV.  Mostly patients had severe preeclampsia, but no maternal death found.  There were neonati problems recorded, which were intrauterine fetal retardation, intrauterine fetal death and premature. It is recommended to give education to the pregnant women to do their antenatal care periodically, especially with previous hystory of preeclampsia or with hypertension problem and young girl about anemia especially with ferrous deficiency problem and the adequate nutrition to be consumed.  It also a good idea to have blood pressure monitoring device at home and know to use it in order to monitor the blood pressure more often in pregnancy period.